Current understanding of bipolar disorder: Toward integration of biological basis and treatment strategies. Issue 9 (23rd May 2019) - Kato, Tadafumi
Abstract : Biological studies of bipolar disorder initially focused on the mechanism of action for antidepressants and antipsychotic drugs, and the roles of monoamines (e.g., serotonin, dopamine) have been extensively studied. Thereafter, based on the mechanism of action of lithium, intracellular signal transduction systems, including inositol metabolism and intracellular calcium signaling, have drawn attention. Involvement of intracellular calcium signaling has been supported by genetics and cellular studies. Elucidation of the neural circuits affected by calcium signaling abnormalities is critical, and our previous study suggested a role of the paraventricular thalamic nucleus. The genetic vulnerability of mitochondria causes calcium dysregulation and results in the hyperexcitability of serotonergic neurons, which are suggested to be susceptible to oxidative stress. Efficacy of anticonvulsants, animal studies of candidate genes, and studies using induced pluripotent stem cell‐derived neurons have suggested a relation between bipolar disorder and the hyperexcitability of neurons. Recent genetic findings suggest the roles of polyunsaturated acids. At the systems level, social rhythm therapy targets circadian rhythm abnormalities, and cognitive behavioral therapy may target emotion/cognition (E/C) imbalance. In the future, pharmacological and psychosocial treatments may be combined and optimized based on the biological basis of each patient, which will realize individualized treatment.